Usage behavior among paywave card users in Kuala Lumpur - Raja Zaharudin, Raja Zahrul Azha; Rashid, Umi Kartini; Nasuredin, Juzaimi; Abu Seman, Noor Aslinda (IJR, 2018)
PayWave cards are used to make contactless payment be faster. However, the issues on data theft has been questioned by the bank's union. This study has been developed to identify the level of usage of payWave cards among consumers in Kuala Lumpur, as well as identifying the relationship between data security and data privacy towards the usage behavior of the payWave cards. A total of 204 data were collected through questionnaires and Statistical Package for Social Science (SPSS) had been used to analyze the data. The level of usage of payWave cards among consumers in Kuala Lumpur was found moderate. Meanwhile, there was a significant relationship between the data security and privacy and the usage behavior towards payWave cards. The findings of this study enhance the knowledge regarding payWave cards and provide practical contributions to the banking institutions and policy makers in increasing the use of payWave cards among consumers.